PENGEMBANGAN BAHAN AJAR MATEMATIKA SD BERNUANSA MOTIF BATIK BATAK - Kiki Pratiwi; Sukmawarti Sukmawarti (Jurnal Inovasi Penelitian, 2022)
The purpose of this study was to describe the procedure for developing elementary mathematics teaching materials with Batak batik motifs, as well as to determine whether elementary school mathematics teaching materials with Batak batik motifs met the criteria for use. This study uses a modification of the ADDIE development model which consists of three stages, namely: (1) the analysis stage (Analysis), (2) the design stage (Design), (3) the development stage (Develop), with the consideration that the researcher focuses on the resulting product. meet the criteria for use. Based on the data analysis, the appropriate teaching materials were obtained through the validity test of material experts, media experts and teacher responses. The results of the validity test by material experts obtained a score of 3.81 with the "Good" category, for media expert 1 the score was 4.5 in the "very good" category, for media experts 2 the score was 4.53 in the "very good" category. while for the teacher's response the score obtained is 3.85 with the "Good" category, it can be calculated that the average score obtained is 4.17 with the "Good" category. Based on the results of the validation of elementary mathematics teaching materials with Batak batik motifs, it can be concluded that elementary school mathematics teaching materials with Batak batik motifs meet the criteria for use.